Role of Nanotechnology in Photocatalysis - Tahir, Muhammad B.; Sohaib, Muhammad; Sagir, Muhammad; Rafique, Muhammad (Encyclopedia of Smart Materials, 2021)
World is facing two major problems, day by day demand of energy and pollution on the planet increasing with the advancement of human activities. These are real problems not only for developing countries but also for developed civilization. Present energy sources are not enough to fulfill the demand of modern world these sources are limited and number of side effects from these. Other major problem pollution that is discussed in this article, very alarming number of population every year affected from pollution and death rate from pollution is very high. In this article, briefly review how photocatalytic technique help us to resolve these problem by environmental friendly, cost effective, less energy consumption and minimum side effect approach. This article cover the main concept about photo-catalysis technique and its related terms. The main feature of efficient photocatalytic activity is selection of photo-catalyst, briefly presentation for which types of nanomaterials are suitable for cost effective and efficient catalytic activity. An overview of application of photocatalytic activity for waste water splitting for H2 production, waste water treatment and air disinfection, which types of catalyst are for these application and briefly discussed factor affecting the catalytic activity.